Dexmedetomidine Combined With Butorphanol or Sufentanil for the Prevention of Post-operative Nausea and Vomiting in Patients Undergoing Microvascular Decompression: A Randomized Controlled Trial - Xu, Guangjun; Zhao, Jing; Liu, Zunyuan; Liu, Guoying; Liu, Lei; Ren, Chunguang; Liu, Yanchao (Frontiers in Medicine, 2020)
Background: Patients undergoing microvascular decompression are often accompanied with high risk of post-operative nausea and vomiting (PONV). In this study, we compare the antiemetic efficacy of butorphanol or sufentanil combined with dexmedetomidine in patients undergoing microvascular decompression. Methods: Patients undergoing microvascular decompression were randomized into two groups. The primary outcome was the occurrence and severity of PONV during the 72 h after surgery. Secondary outcomes included levels of pain intensity and sedation and consumption of opioids at 1, 2, 6, 12, 24, 48, and 72 h after surgery. We also recorded the intraoperative hemodynamics, consumption of narcotic drugs, operation and anesthesia time, estimated blood loss, infusion volume and urine output, requirements of rescue antiemetics or analgesics, the satisfaction scores of patients and surgeons, complications, and length of stay. Results: The overall incidence rates of nausea and vomiting during the 72 h after surgery were significantly reduced in group DB (76.00 and 44.00% in group DS vs. 54.17% and 22.92% in group DB, P < 0.05). Patients in group DB had a lower incidence of nausea than those in group DS at intervals of 1–6 and 6–24 h (P < 0.05). However, patients in group DB had a lower incidence of vomiting than those in group DS only at intervals of 1–6 h (P < 0.05). Similarly, the number of patients requiring rescue antiemetics was also significantly reduced in group DB compared with that in group DS at intervals of 1–6 h (P < 0.05). The number of patients experiencing moderate to severe PONV was comparable between the two groups during 72 h after surgery (P > 0.05). The consumption of opioid morphine equivalent was significantly reduced in group DB (P < 0.05). Compared with those in group DS, the satisfaction scores of both patients and surgeons were significantly increased in group DB (P < 0.05). Conclusion: Butorphanol combined with dexmedetomidine could reduce early PONV and the number of patients requiring rescue antiemetics, especially at intervals of 1–6 h, while the satisfaction scores of both patients and surgeons were significantly increased.